An epidemiological of acute Pesticides poisoning in children presenting in emergency pediatric at Tishreen University Hospital during 2020-2023 - صقور سعاد (Latakia University Journal -Medical Sciences Series, 2023)
Objective: An epidemiological study of acute pesticide poisoning among children under 13 years of age attending in emergency pediatric at Tishreen University Hospital during 2020-2023 regarding to demographic, Prevalence, clinical manifestation, management and outcome. Material and methods: In an Observational Descriptive Cross Sectional Study that included 67 consecutive patients (55.2% males vs. 44.8% females) of children attending Tishreen University Hospital in Lattakia during the period between January 2020 and January 2023 with a story of pesticide ingestion. Results :The majority of cases were from 2-6 years old (62,7%) ,ages between 6-12 years old were (28,4%) ,ages more 12 years old were( 6%,) ages younger 2 years old were ( 3%) .The frequency of poisoning according seasons shows that the majority of poisoning occurred in Summer(43,3%),in Autumn(26,9 %) ,in Spring(25,4%) and in winter( 4,4% ) . Insecticides :Pyrmethr and perytroid were the most common cause of Pesticides poisoning(25,4%) ,then Organophosphate compounds(11,9) , Naphtaline (11,9%) ,Carbamate and Organochlor compounds (7,5 %) ,and finally Chlorfenapyr (3%). Rodenticides:Warfarin was the most common cause (23,8), then Zinc Phosphide (4,5%) , finaly Arsenic (3%).Herbicides :Parquate was (1,5%). - 23 children were admitted in pediatric department (34,3%) and 5 children were admitted in the intensive care unit (7,5%). No deaths recorded Symptoms and clinical signs: vomiting and abdominal pain were in 25 cases (37,3%) ,coma was in 12 cases (18%) ,miosis was in 12 cases (18%) ,cough , acute renal failure were in 1 case (1,5%) , bronchospasm was in 3 cases (4,5%) ,upper digestive hemorrhage , epistaxis, anemia were in 1 case (1,5%). Gastric lavage was performed in 44 cases (65,7%) ,Activated charcoal was given in 30 cases (44,8%) . specific Antidots were used in 27 cases (40%) 13 of them recived Atropin(19,4%), 8 recived Pralidoxim (12%),14 recived Vitamin K1 (preventive dose 10 mg one dose ) ( 12%) and 1 child resived Vk1( therapeutic dose 10mg x 4 for 3 days)(1,5%).Oral ingestion was the main rout of toxicity in our study (92%), by inhalation it was in ( 4,5%) and the dermal rout was in (4,5 %). 83,6 % of cases were indoors .There was no mortality in our study .